Effectiveness Of High Fowler Position and Pursed Lip Breathing Therapy In Ckd Patients - Ratna, Sri; Tohri, Tonika (Jambura Nursing Journal, 2026)
Chronic Kidney Disease (CKD) is a chronic condition characterized by a progressive and irreversible decline in kidney function, which can lead to various systemic complications. Reduced kidney function causes fluid retention and activation of the renin–angiotensin–aldosterone system, thereby increasing cardiac workload. In the long term, this condition can result in congestive heart failure (CHF), which further triggers an increase in pulmonary capillary hydrostatic pressure and leads to pulmonary edema in the alveoli. CKD patients who develop CHF with pulmonary edema require management beyond pharmacological therapy, namely through non-pharmacological nursing interventions such as the application of the high fowler position and pursed-lip breathing exercises. The purpose of this study is to determine the effectiveness of applying the high fowler position and pursed-lip breathing on improving respiratory status in CKD patients complicated by CHF with alveolar pulmonary edema. The method used is a case study with a nursing process approach, including assessment, determination of nursing diagnoses, planning, implementation, and evaluation. Data were collected through interviews, observation, physical examination, and documentation and literature review. The results of nursing care showed improvement in respiratory status after the application of the high fowler position and pursed-lip breathing exercises, indicated by decreased respiratory rate, reduced dyspnea complaints, increased oxygen saturation, and the disappearance of additional breath sounds. It is concluded that the application of the high fowler position and pursed-lip breathing exercises contributes to the improvement of respiratory status in CKD patients complicated by CHF with alveolar pulmonary edema.